2010
DOI: 10.1519/jsc.0b013e3181d1d318
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Changes in Performance and Inflammatory Responses After Acute Plyometric Exercise

Abstract: The objectives of the present investigation were to study the inflammatory and performance responses after an acute bout of intense plyometric exercise during a prolonged recovery period. Participants were randomly assigned to either an experimental group (P, n = 12) that performed intense plyometric exercises or a control group (C, n = 12) that rested. The delayed onset of muscle soreness (DOMS), knee range of motion (KROM), creatine kinase (CK) and lactate dehydrogenase (LDH) activities, white blood cell cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
105
7
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 28 publications
16
105
7
6
Order By: Relevance
“…Leukocytes exhibit a transient rise immediately post exercise followed by decreased at 24 hours later. This data is similar with previous study that had been done on plyometric training 12,22 .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Leukocytes exhibit a transient rise immediately post exercise followed by decreased at 24 hours later. This data is similar with previous study that had been done on plyometric training 12,22 .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast other research on plyometric exercise suggested that CRP increased only 2 days after training 22 . In other hands CRP production in our investigation is lower than plyometric and severe exercise 12,26 that it is same with the study on resistance or aerobic exercise 27 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations